Notoedres Cati Infestation in a Cat and its Management: A Case Report - Ansari, Siraj; Dabas, Ravi; Rajpurohit, Vinita; Yadav, Asha; Dehru, Shruti (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Notoedric mange is a highly contagious and pruritic skin disease caused by burrowing mites Notoedres cati of family Sarcoptidae. Notoedric cati primarily affects cats, although it can also affect humans and other species. Present paper deals with clinical signs, diagnosis, and treatment of Notoedric mange in a kitten, aged about three and half months. In this case report, 1 kg male Persian kitten was presented to the Referral Veterinary Polyclinic of ICAR- Indian Veterinary Research Institute (IVRI), Izatnagar with a complaint of itching and alopecia for past 15 days. On physical examination skin thickening, dry crusty and scaly lesions on the face, neck and limbs could be noticed. The appetite and defecation was normal and all the clinical parameters (rectal temperature, pulse rate, heart rate etc.) were within the normal range. On laboratory examination, skin scraping was positive for Notoedres cati. Based on the history, clinical manifestations and skin scraping examination, the case was diagnosed as Notoedres cati infestation. Therapeutic management was done with Inj. ivermectin @ 200 μg/kg, b. wt, subcutaneously once in a week for four weeks along with supportive therapy by oral administration of antihistamine hydroxyzine hydrochloride @ 2.2 mg/kg b. wt thrice in a day and supplementation of multivitamin, minerals, omega 3 and omega 6 fatty acids. Owner was advised to give bath with benzyl peroxide shampoo twice in a week. Kitten showed some improvement following the second dose of ivermectin, and complete remission of clinical signs was noticed following the fourth treatment.